2005
DOI: 10.22146/agroekonomi.16951
|View full text |Cite
|
Sign up to set email alerts
|

Keunggulan Kompetitif Usaha Ternak Sapi Potong Di Kabupaten Gunungkidul

Abstract: The research has been conducted to find out a competitive advantage of beef cattle farming. Data used in this research was primary data collected through survey in Gunungkidul Regency, Province od Daerah Istimewa Yogyakarta. The location determination was cinducted in purposive based on population of beef cattle. The selected location was Sub District of Karang Mojo and Semanu. Total sample was defined in quota that is 240 beef cattle farmers, each 120 beef cattle farmers in Karang Mojo and Semanu. Sample sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Widodo (2006) showed the management of Sistem Integrasi Peternakan Sapi (Cattle Farming Integration System, CFIS) has a comparative advantage with an indicator of domestic resources cost coefficient (DRCC) of 0.57. Sunandar (2006) conducted a study in Gunung Kidul district found that the business of beef cattle in Gunung Kidul has no comparative advantages with DRCC value larger than one (DRCC>1). Analysis by Handayani (2013) using policy analysis matrix (PAM) suggests that the business of cattle fattening or breeding in Indragiri Hulu district has a competitive and comparative advantage.…”
Section: Introductionmentioning
confidence: 99%
“…Widodo (2006) showed the management of Sistem Integrasi Peternakan Sapi (Cattle Farming Integration System, CFIS) has a comparative advantage with an indicator of domestic resources cost coefficient (DRCC) of 0.57. Sunandar (2006) conducted a study in Gunung Kidul district found that the business of beef cattle in Gunung Kidul has no comparative advantages with DRCC value larger than one (DRCC>1). Analysis by Handayani (2013) using policy analysis matrix (PAM) suggests that the business of cattle fattening or breeding in Indragiri Hulu district has a competitive and comparative advantage.…”
Section: Introductionmentioning
confidence: 99%